PENGARUH LUAS PERMUKAAN ELEKTRODA DENGAN PENAMBAHAN PWM CONTROLLER TERHADAP EFISIENSI PRODUKSI GAS HIDROGEN PADA PROSES ELEKTROLISIS - Fitriyanti, Fitriyanti (SAINFIS: Jurnal Sains Fisika, 2021)
This research makes an electrolysis device with the aim of separating oxygen gas (O2) and Hydrogen (H2) or known as an HHO generator. The HHO generator designed in this study is to determine how much influence the cathode and anode cross-sectional areas are used in the electrolysis process. The power source needed in the electrolysis process in this study uses a battery with a current of 3 Ampere and a voltage of 12 Volts. With the addition of a PWM controller, the resulting current and voltage can be increased by 6.3 Ampere and 38 Volts. Based on the results obtained by adding a PWM controller and increasing the cross-sectional area of the electrode plate can increase the productivity of hydrogen gas produced. By increasing the size of the cathode and anode plates require more power to produce optimal effectiveness. The electrode cross section of 20 cm3 has an effectiveness of 5.959% and a cross-sectional area of 40 cm3 has the highest effectiveness of 8.127%. The effectiveness of a tool affects the power used, the greater the power required, the effectiveness of the tool will decrease because it requires greater electricity consumption in the operation of the tool, but with an increased flow rate of gas production. The maximum effectiveness obtained is 8.127% with 36 watts of power, and the lowest is 1.786% by increasing the power to 239.4 watts at an electrode area of 40 cm3